Characterization of a L-Gulono-1,4-Lactone Oxidase Like Protein in the Floral Nectar of Mucuna sempervirens, Fabaceae - Zhou, Hong-Xia; Milne, Richard I.; Ma, Xue-Long; Song, Yue-Qin; Fang, Jian-Yu; Sun, Hang; Zha, Hong-Guang (Frontiers in Plant Science, 2018)
Floral nectar plays important roles in the interaction between animal-pollinated plants and pollinators. Its components include water, sugars, amino acids, vitamins, and proteins. Growing empirical evidence shows that most of the proteins secreted in nectar (nectarins) are enzymes that can tailor nectar chemistry for their animal mutualists or reduce the growth of microorganisms in nectar. However, to date, the function of many nectarins remains unknown, and very few plant species have had their nectar proteome thoroughly investigated. Mucuna sempervirens (Fabaceae) is a perennial woody vine native to China. Nectarins from this species were separated using two-dimensional gel electrophoresis, and analyzed using mass spectrometry. A L-gulonolactone oxidase like protein (MsGulLO) was detected, and the full length cDNA was cloned: it codes for a protein of 573 amino acids with a predicted signal peptide. MsGulLO has high similarity to L-gulonolactone oxidase 5 (AtGulLO5) in Arabidopsis thaliana, which was suggested to be involved in the pathway of ascorbate biosynthesis; however both MsGulLO and AtGulLO5 are divergent from animal L-gulonolactone oxidases. MsGulLO was expressed mainly in flowers, and especially in nectary before blooming. However, cloning and gene expression analysis showed that L-galactonolactone dehydrogenase (MsGLDH), a vital enzyme in plant ascorbate biosynthesis, was expressed in all of flowers, roots, stems and especially leaves. MsGulLO was purified to near homogeneity from raw MS nectar by gel filtration chromatography. The enzyme was determined to be a neutral monomeric protein with an apparent molecular mass of 70 kDa. MsGulLO is not a flavin-containing protein, and has neither L-galactonolactone dehydrogenase activity, nor the L-gulonolactone activity that is usual in animal GulLOs. However, it has weak oxidase activity with the following substrates: L-gulono-1,4-lactone, L-galactono-1,4-lactone, D-gluconic acid-δ-lactone, glucose, and fructose. MsGulLO is suggested to function in hydrogen peroxide generation in nectar but not in plant ascorbate biosynthesis.